Calretinin and parvalbumin in schizophrenia and affective disorders: A mini-review, a perspective on the evolutionary role of calretinin in schizophrenia, and a preliminary post-mortem study of calretinin in the septal nuclei. - Ralf eBrisch; Hendrik eBielau; Arthur eSaniotis; Arthur eSaniotis; Rainer eWolf; Bernhard eBogerts; Bernhard eBogerts; Dieter eKrell; Johann eSteiner; Johann eSteiner; Katharina eBraun; Katharina eBraun; et al. (Frontiers in Cellular Neuroscience, 2015)
2.Objective: The septal nuclei are important limbic regions that are involved in 3.emotional behavior and connect to various brain regions such as the habenular 4.complex. Both the septal nuclei and the habenular complex are involved in the 5.pathology of schizophrenia and affective disorders.6. Methods: We characterized the number and density of calretinin-immunoreactive 7.neurons in the lateral, medial, and dorsal subregions of the septal nuclei in three 8.groups of subjects: healthy control subjects (N = 6), patients with schizophrenia (N 9.= 10), and patients with affective disorders (N = 6). 10.Results: Our mini-review of the combined role of calretinin and parvalbumin in 11.schizophrenia and affective disordres summarizes18 studies. We did not observe 12.significant differences in the numbers of calretinin-immunoreactive neurons or 13.neuronal densities in the lateral, medial, and dorsal septal nuclei of patients with 14.schizophrenia or patients with affective disorders compared to healthy control 15.subjects. 16.Conclusions: Most post-mortem investigations of patients with schizophrenia have 17.indicated significant abnormalities of parvalbumin-immunoreactive neurons in 18.various brain regions including the hippocampus, the anterior cingulate cortex, and 19.the prefrontal cortex in schizophrenia. This study also provides an explanation 20.from an evolutionary perspective for why calretinin is affected in schizophrenia.